Research of influence of biological activation on the vitamin complex of grain cereal cultures - Bazhay-Zhezherun, Svitlana; Bereza-Kindzerska, Ludmyla; Togachynska, Olga (My University, 2017)
We offered to hydrothermal treatment processing grain of cereal cultures - wheat, bare grain oats, triticale, which promotes increase in its nutritional value, in particular increase in amount of vitamins, by biological activation. . In the course of the offered grain preparation contents of anti-mineral substance of phytin significantly decrease, the content of vitamins of antioxidants, of vitamins of group B, of inositol considerably grows.
Keywords: біологічна активація; пророщені зерна; вітаміни; пшениця; горіння овес; тритикале; биологическая активация; пророщенное зерно; витамины; пшеница; голозерный овес; biological activation; germinated grain; vitamins; wheat; bare grain oats; triticale; кафедра технології оздоровчих продуктів; кафедра екології та екоменеджменту